Use of Spent Coffee Ground Compost in Peat-Based Growing Media for the Production of Basil and Tomato Potting Plants. Issue 3 (4th February 2016) - Ronga, Domenico; Pane, Catello; Zaccardelli, Massimo; Pecchioni, Nicola
ABSTRACT: A spent coffee ground compost (SCGC) was evaluated as an alternative component of growing media to partially replace commercial peat (CP) and fertilizers in the production of potted plants. Seven mixtures (CP 100% + solid mineral fertilizers, CP 100% + liquid mineral fertilizers, CP 90% + SCGC 10%, CP 80% + SCGC 20%, CP 70% + SCGC 30%, CP 60% + SCGC 40%, and CP 100% without fertilizers) were compared for the production of basil and tomato potted plants. SCGC used in a proportion up to 40% enhanced the general plant stand by affecting the dry weight and the measured foliar parameters. Tomato and basil recorded good growth rates on SCGC-amended media, showing quality indices similar to those obtained under fertilization, evidencing compost plant nutrition provision. SCGC appears to be suitable for application as a partial peat substitute in the production of potted plants.